2007
DOI: 10.1016/j.matbio.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XI chain misassembly in cartilage of the chondrodysplasia (cho) mouse

Abstract: Molecular mechanisms controlling the assembly of cartilage-specific types II, IX and XI collagens into a heteropolymeric network of uniformly thin, unbanded fibrils are not well understood, but collagen XI has been implicated. The present study on cartilage from the homozygous chondrodysplasia (cho/cho) mouse adds support to this concept. In the absence of α1(XI) collagen chains, thick, banded collagen fibrils are formed in the extracellular matrix of cho/cho cartilage. A functional knock-out of the type XI co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…Such abnormal large fibrils were also described in the cho cartilage (Seegmiller and Monson, 1982;Li et al, 1995). In cho mice, an alternative hybrid collagen XI molecule was shown to assemble in which the closely related collagen V α1 chain replaces the missing collagen XI α1 chain (Fernandes et al, 2007). They concluded that the At 15 hpf, dlx2a is expressed in the three neural crest streams in wild type embryos (C) and in morphants (D) though reduced signal is observed.…”
Section: Collagen XI α1 Knockdown Affects Zebrafish Extracellular Matmentioning
confidence: 75%
“…Such abnormal large fibrils were also described in the cho cartilage (Seegmiller and Monson, 1982;Li et al, 1995). In cho mice, an alternative hybrid collagen XI molecule was shown to assemble in which the closely related collagen V α1 chain replaces the missing collagen XI α1 chain (Fernandes et al, 2007). They concluded that the At 15 hpf, dlx2a is expressed in the three neural crest streams in wild type embryos (C) and in morphants (D) though reduced signal is observed.…”
Section: Collagen XI α1 Knockdown Affects Zebrafish Extracellular Matmentioning
confidence: 75%
“…Individual collagen ␣-chains were cut out and subjected to ingel trypsin digestion (26). Electrospray MS was performed on the tryptic peptides using an LCQ Deca XP ion trap mass spectrometer equipped with in-line LC (ThermoFinnigan) using a C8 capillary column (300 ϫ 150 mm; Grace Vydac 208MS5.315) eluted at 4 l/min.…”
Section: Methodsmentioning
confidence: 99%
“…In the lower left panel, the α1(XI) N-telopeptide antiserum selectively bound to the α3(XI) α-chain on a Western blot and the α2(XI) N-telopeptide antiserum to the α1(XI) α-chain. These antisera can be used to determine the molecular binding partners of the N-telopeptides of type XI collagen chains present in more complex cartilages [28] or, for example, engineered tissue constructs induced in vivo or grown in vitro.…”
Section: Collagen Type XImentioning
confidence: 99%